Existential risk from AI and orthogonality: Can we have it both ways?. (15th July 2021) - Müller, Vincent C.; Cannon, Michael
Abstract: The standard argument to the conclusion that artificial intelligence (AI) constitutes an existential risk for the human species uses two premises: (1) AI may reach superintelligent levels, at which point we humans lose control (the 'singularity claim'); (2) Any level of intelligence can go along with any goal (the 'orthogonality thesis'). We find that the singularity claim requires a notion of 'general intelligence', while the orthogonality thesis requires a notion of 'instrumental intelligence'. If this interpretation is correct, they cannot be joined as premises and the argument for the existential risk of AI turns out invalid. If the interpretation is incorrect and both premises use the same notion of intelligence, then at least one of the premises is false and the orthogonality thesis remains itself orthogonal to the argument to existential risk from AI. In either case, the standard argument for existential risk from AI is not sound.—Having said that, there remains a risk of instrumental AI to cause very significant damage if designed or used badly, though this is not due to superintelligence or a singularity.